Effect of indole-3-butyric acid on rooting of phytoplasma-recovered and healthy periwinkle Catharanthus roseus (L.) G. Don - Ćurković-Perica, Mirna (Array, 2008)
Abstract: After prolonged treatment with the auxin, indole-3-butyric acid (IBA), the rooting efficiency of healthy C. roseus shoots was compared with recovered shoots containing a high titer of 'Candidatus Phytoplasma' species 'Ca. P. ulmi' and 'Ca. P. solani' and recovered shoots in which, upon IBA-treatment, 'Ca. P. asteris' was undetectable or present in low titer. On a medium containing the same concentration of IBA, the number of rooted shoots decreased with statistical significance, following the trend: healthy shoots > 'Ca. P. asteris'-recovered shoots > 'Ca. P. ulmi' and 'Ca. P. solani'-recovered shoots. Furthermore, after the rooting experiment, 'Ca. P. asteris' was detected in all the tested unrooted shoots while, among the rooted periwinkles, only 20 % were positive. These results constitute the first report in which a correlation between the presence of phytoplasmas and rooting efficiency of the periwinkle host has been shown. Since auxins are phytohormones involved in the initiation and emergence of adventitious roots, reduced rooting efficiency may reflect disturbed levels or transport of auxin(s) in phytoplasma-infected periwinkles